Verbal Complementizers in Arabic - Ahmed, Hossam Eldin Ibrahim (ProQuest LLC, 2015)
A class of Modern Standard Arabic complementizers known as "'?inna' and its sisters" demonstrate unique case and word order restrictions. While CPs in Arabic allow both Subject-Verb (SV) and Verb-Subject (VS) word order and their subjects show nominative morphology, CPs introduced by "?inna" ban a verb from directly following the complementizer. Preverbal subjects in "?inna" clauses show accusative case marking, while postverbal subjects show nominative morphology. Previous research explains these restrictions as default case or Multiple Case Assignment, both problematic for Case Theory as they violate the Activation Principle. This dissertation explains word order and case effects of "?inna" within the framework of Phase Theory and Feature Inheritance (FI). Morphological, historical, and usage evidence point out that "?inna"-type complementizers have verbal properties similar to illocutionary verbs. Taking Case to be a reflection of phi features that T heads receive from higher heads (e.g. Complementizers) via Feature Inheritance, the nominative-accusative alternation on preverbal subjects can be attributed to the selection of C heads: phi features on null complementizers and conditionals reflect as NOM, while phi features on Verbal Complementizers (VCs) reflect as ACC. VCs show similar Case behavior to the English Prepositional Complementizer for. They differ in distribution; while for only introduces a subordinate clause, and takes infinitival TP complements, VCs introduce a matrix clause and require finite TP complements, lending stronger support to Feature Inheritance theory than English for. Nominative postverbal subjects in "?inna" clauses are explained as an effect of antiagreement at Spell-Out. Postverbal subjects and the Case probe on T are PF local, allowing for impoverished case agreement. Preverbal subjects and the Case licenser belong to different Phonological Phrases. To satisfy the Recoverability Condition, full case agreement is required between T and the subject, resulting in accusative morphology on the subject. Finally, the requirement that "?inna"-clauses have an intervener between "?inna" and the verb is explained by associating the full phi features of "?inna" with the EPP. As the phi set is inherited from "?inna" to T, the EPP property is satisfied by the preverbal subject or by adverbial intervening between "?inna" and the verb. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]